التحسينات المصحفية من خلال المحكم في نقط المصاحف للإمام -أبو عمرو الداني- - لجدل علي, حسينة (University of eloued جامعة الوادي, 2022)
"كتب القرآن الكريم زمن النبوة خالياً من النقط والشكل والهمزات على عادة العرب في الكتابة آنذاك، ولم يكن ذلك يشكل عليهم في قراءتها، ومع انتشار الإسلام، ودخول الأعاجم، بدأ يظهر اللحن في اللغة العربية مما دعا العلماء إلى وضع علامات للإعراب، فقام أبو الأسود الدؤلي بنقط المصحف نقط إعراب، ونقط بعده نصر بن عاصم الليثي نقط الإعجام، وغير الخليل نقط الإعراب إلى حروف صغيرة، ومن هذا قيض الله بفضله وكرمه وحكمته لهذا العلم رجالاً أوفياءَ، وعلماء أجلاء، أقبلوا عليه تعلماً وتعليماً، وقراءة وإقراءً، وتأليفاً وتصنيفاً. منهم الإمامُ أبو عَمرو الداني(ت444ه). قد اتَّسم- رحمه الله – بظهور شخصيَّته ومنهجه في كتابه المحكم وذلك في تحقيق وتدقيق وفحص روايات علم ضبط المصاحف. لذا أحببتُ، بعد اختياري. وقد سعيت بمحاولة جهدي البحث للإجابة على عدة إشكالات والبحث يستقري التحسينات المصحفية التي دخلت المصاحف سواء كانت باللون أو بالحرف أو برمز من خلال كتاب المحكم للإمام لأبي عمرو الداني المراد الله تعالى، ووصلت في ختامه ببعض النتائج والتوصيات. ""The Holy Quran was written at the prophecy time، free of dots، vowelization، and glottal stops، according to the Arabs’ custom of writing at the time، and that did not constitute an obstacle for them to read it، and via the spread of Islam، and the entry of non-Arabs، the grammatical mistakes began to appear in the Arabic language، and that prompted scholars to put signs for articulation. Therefore، Abu El-Aswad Al-Dou’ali marked the Qur’an with the dots of the articulation، after him Nasr ben Asim El-Laythi did the dots of the letters، as well as El-Khalil had changed the dots of the parsing into lowercase letters. Proceeding from this، Allah Almighty، by His grace، generosity، and wisdom، placed for this science loyal men and eminent scholars، who paid attention to it in terms of learning، teaching، reading، and making athers read، composition and classification. And among these scholars was El imam Abu Amro El-Dani (d. 444 AH)، who was distinguished - may Allah Almighty have mercy on him - by the appearance of his personality and approach in his arbitrator book throughout investigation، scrutiny and examination the narratives of the science of controlling manuscripts. So I liked following my choice and did my best to research in order to answer several problems. The research was delving into the manuscripts' improvements that entered the Qur'an، whether by gendre، letter، or symbol through the arbitrator book of El imam Abou Amro El-Dani، which was intended for Allah Almighty، and in its conclusion I came to some findings and recommendations."
علوم قرأن
Keywords: التحسينات المصحفية - المحكم في نقط المصاحف - أبو عمرو الداني.; The journalist-the arbitrator in the points of the Qur'an-Abu Amr al-Dani.